Answer:
Explanation:
Given system of equations,
As per statement,
Isolating the variable y in the first equation,
Now, substituting into the second equation,
Which is the resulting equation,
Simplifying the equation,
The resulting equation is
x^2/4+16x^2/9=1
The given equations are:
3y=12x eq(1)
x^2/4+y^2/9=1 eq(2)
We need to isolate variable y in equation 1
Divide both sides of the equation with 3
3y/3 = 12x/3
y = 4x
Now, substitute the value of y=4x in second equation
x^2/4+y^2/9=1
x^2/4 + (4x)^2/9 = 1
5.8m questions
7.5m answers